PERBEDAAN TINGKAT STRES ANTARA KARYAWAN PRODUKSI DAN KARYAWAN NON PRODUKSI PT. BARA JAYA ENERGY SITE BANTUAS - Annisa, Dwi Rizqi (MOTIVASI, 2013)
ABSTRACThis study aims to determine whether there are differences in stress levels between production employees and non-production employees. this Stress question is stress that occurs in a place of work is commonly called job stress. Stress can show up on all aspects of human life, including the stress found on occupations commonly called job stress. Each individual has a level stress and have a different way of dealing with stress between each other.This study was conducted at a coal mining company. The subjects were employees of PT. Bara Jaya Energy which amounted to 158 people consisting of 79 production employees and 79 non-production employees. This study consisted a single variable, which is job stress. this data collection using method scale, with job stress scale measuring instrument consisting of a 32 point statement. Data analysis techniques using t-test, with help of statistical program SPSS version 13. The results were obtained value of t = -2795 and p = 0.006 (p <0.05), and mean values for production employees was 67.15, while the non-production employees at 63.03. This indicated that there are differences in the level of stress among employees of production and non-production employees with value